Hemopericardium with Subdural Hemorrhage: A Rare Case - Bhoi, S B; Shinde, D K; Chandekar, K S; Mahajan, N P; Tumram , N K (Journal of Indian Academy of Forensic Medicine, 2014)
The incidence of simultaneous occurrence of intracranial hemorrhage and hemopericardium due  to the rupture of a dissecting aneurysm is very rare. We describe an autopsy case of a 52-year-old male  with hypertension who died suddenly. He had been treated for hypertension. During post-mortem  examination we found pericardial cavity filled with blood and blood clots. This hemopericardium was due  to rupture of dissecting aortic aneurysm. Ascending aorta shows ruptured dissecting aortic aneurysm [De  Bakey type 2]. Intramural hematoma present in the wall of ascending aorta. Histologically, the wall of the  aneurysm revealed cystic medial necrosis, which appears to idiopathic in nature. There was also  evidence of subdural hemorrhage. After analyzing the findings the opinion as to the cause of death was  “Hemopericardium due to rupture of dissecting aortic aneurysm along with intracranial bleeding.” As per  our view in present case the subdural hemorrhage was occurred after the rupture of dissecting aortic  aneurysm when the venous pressure increases, leading to the rupture of bridging vein in subdural space.
Keywords: Intracranial Hemorrhage; Hemopericardium; Post-mortem; Aortic Aneurysm